2011
DOI: 10.1002/aic.12505
|View full text |Cite
|
Sign up to set email alerts
|

Nickel phosphide catalyst for autothermal reforming of surrogate gasoline fuel

Abstract: An investigation into the catalytic autothermal reforming (ATR) of a mixture of n-octane and naphthalene (6 wt %), designed as a surrogate gasoline, is undertaken. Carbon deposition on the metallic Ni catalyst has been aware of the main hurdle for the catalytic reforming of hydrocarbons especially those with high carbon numbers. This work develops Ni x P y crystallites on a CeO 2 powder support by electroless nickel plating and calcination. The catalyst exhibits nil coking extent after reforming the surrogate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…60 Liu et al suggested that Ce 4þ ions on the surface of support can oxidize the deposited coke to form Ce 3þ ions in the presence of NiP nanoparticles, leading to the formation of oxygen vacancies. 61 da Silva et al examined the effect of support reducibility on the stability of ESR and concluded that the high oxygen/OH mobility of the CeO 2 support contributed to the high stability and reactivity of the catalyst. 62 Laosiripojana et al proposed that enhanced redox properties of doped ceria prevented carbon deposition by oxidizing the adsorbed surface hydrocarbons on nickel surface.…”
Section: Nickel Catalystsmentioning
confidence: 98%
“…60 Liu et al suggested that Ce 4þ ions on the surface of support can oxidize the deposited coke to form Ce 3þ ions in the presence of NiP nanoparticles, leading to the formation of oxygen vacancies. 61 da Silva et al examined the effect of support reducibility on the stability of ESR and concluded that the high oxygen/OH mobility of the CeO 2 support contributed to the high stability and reactivity of the catalyst. 62 Laosiripojana et al proposed that enhanced redox properties of doped ceria prevented carbon deposition by oxidizing the adsorbed surface hydrocarbons on nickel surface.…”
Section: Nickel Catalystsmentioning
confidence: 98%
“…Hence, the effect of CeO 2 addition to Pt/Al 2 O 3 catalyst is only the improvement of initial conversion and elimination of coke formation. Liu et al proposed that the Ce 4+ ions on the CeO 2 surface can oxidize the coke formed while being reduced to Ce 3+ . Laosiripojana et al suggested that the strengthened redox property of doped CeO 2 suppressed coke formation by oxidizing the hydrocarbons on metal surface and then contributed to the higher catalytic stability .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction property of nitrogen monoxide was also investigated over the Cu/(active carbon) catalyst, which copper component was loaded onto the active carbon by the electroless plating [22,23]. Furthermore, the reforming property of hydrocarbon (n-octane) over the Ni/CeO 2 catalyst, which deposited a nickel component onto cerium oxide by the electroless plating, was investigated [24]. However, all catalysts prepared by these researches were granular type, and were not a structured (plate) type that can be used in the wall-type reaction system.…”
Section: Introductionmentioning
confidence: 99%